2016
DOI: 10.1080/10826084.2016.1197259
|View full text |Cite
|
Sign up to set email alerts
|

Anger Expression Style Predicts the Domain of the First Smoking Relapse After a Quit Attempt

Abstract: Background-Risk for smoking relapse may be associated with context-dependant social and behavioral cues. However, lack of research examining the role of trait negative mood such as anger in this relationship and assessment of objective indices related to smoking status (e.g., biochemical measures) may limit existing findings. We examined the roles of trait anger, habitual anger expression behavior, and the situation in which the first incident of smoking lapse following a quit attempt occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
2
2
0
2
Order By: Relevance
“…In fact, findings between the two studies may differ because the outcomes differed (incident events including fatal and nonfatal cases versus mortality including secondary events) and the current analyses introduced a 2-year lag to lower concerns about reverse causation. More generally, the association of greater aggressive expression with higher mortality risk is consistent with evidence pointing to the detrimental role of aggressively expressing anger in various chronic disease risk and unfavorable biobehavioral processes involved in mortality risk (13,14,18). Other maladaptive strategies for regulating anger, like suppression, have also been related to greater mortality risk (21,22).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In fact, findings between the two studies may differ because the outcomes differed (incident events including fatal and nonfatal cases versus mortality including secondary events) and the current analyses introduced a 2-year lag to lower concerns about reverse causation. More generally, the association of greater aggressive expression with higher mortality risk is consistent with evidence pointing to the detrimental role of aggressively expressing anger in various chronic disease risk and unfavorable biobehavioral processes involved in mortality risk (13,14,18). Other maladaptive strategies for regulating anger, like suppression, have also been related to greater mortality risk (21,22).…”
Section: Discussionsupporting
confidence: 79%
“…Behavioral and biological sequelae of anger may matter for some more than other health outcomes and have been postulated as key mechanisms linking anger to such outcomes (9,11,12). Previous investigations of the anger-life-style linkage, albeit limited, suggested higher trait anger was associated with subsequent heavy drinking (13), whereas greater aggressive expression was related to future smoking relapse (14). Prior biological studies showed relationships of severe/frequent angry feelings with arrhythmia (15) and less favorable blood pressure patterns (16) hours later, and higher aggressive expression levels with 4-year hypertension risk (17) and elevated glucose 9 years later (18).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we found evidence that high trait anger was associated with increased risk for early relapse. These findings are consistent with acute effects of stress in smokers and other substance users (178, 239, 240); and the findings indicate that high levels of trait anger predispose individuals to experience greater emotional intensity during withdrawal, possibly contributing to mood difficulties and vulnerability for drug use and early relapse.…”
Section: Moderators Of the Blunted Stress Response In Nicotine Addictionsupporting
confidence: 78%
“…Los resultados obtenidos, siguen la línea de otros estudios que demuestran que el consumo de tabaco se relaciona con poseer mayores niveles de ira rasgo y sus variables (Bongard et al, 2016;Matsuda et al, 2015;Powers et al, 2016;Smits et al, 2016;Whalen et al, 2001); pero en este caso los resultados se replican en población deportista, en la cual no se han encontrado estudios previos que examinen estas variables. (Altin, 2015;Buchman et al, 1991;Hassmén et al, 2000).…”
Section: Discusión Y Conclusionesunclassified
“…En este trabajo de investigación, la función catártica que tiene el ejercicio físico no se muestra en los deportistas fumadores (Delgado y Tercedor, 2002 Bongard et al, 2016;Kalman, 2002;Kenford et al, 2002;Smits et al, 2016;Whalen et al, 2001). En este estudio se examinan la ira rasgo y sus variables, y no se encuentran relación entre el número de cigarrillos diarios y los niveles de ira en deportista, a diferencia de los estudios que han encontrado que el consumo de tabaco aumenta los niveles de ira rasgo en población general (Bongard et al, 2016;Whalen et al, 2001). …”
Section: Discusión Y Conclusionesunclassified